Web Usage Mining Architecture and Applications (Global Journal of Computer Science and Technology, 2012)
The WEBMINER is a system that implements parts of this general architecture. The first part is domain dependent application. The second part is the domain independent application. This includes pattern discovery and analysis as part of the system's data mining engine. The overall architecture for the Web mining process is depicted below: